Clinical and Host Related Factors Influencing Prevalence of Tuberculosis in Bumula Sub County, Bungoma County in Kenya - Magomere, Robert Shihuzire; Angira, Charles Helm Obiero; Konyole, Silvenus Ochieng (Academia, 2019)
Robert Shihuzire Magomere, , Tuberculosis (TB) is an infectious bacterial disease caused by bacillus Mycobacterium tuberculosis. Globally 9.6 million people fell ill with TB and 1.5 million died from the disease in 2014. Bumula Sub-County had 200 patients diagnosed with TB in 2016, with a case notification rate of 454 cases per 100,000 people. The main objective of this study was to establish the clinical and host related factors influencing prevalence of TB in Bumula Sub County. Methodologically, this study applied a descriptive design that was cross sectional in nature. Data was collected using a researcher to respondent administered questionnaire; Data was collected from 200 respondents and was analyzed using Statistical Package for Social Sciences version 20 and presented in narratives and tables’ forms. The findings of this study revealed that respondents were aged between 15 to 77 years of age, the median age was 42 and the mean age was 42.92 ± 1.133. Males were 56.5% (113/200). Previous history of TB (χ2=7.772, df=1, p=0.005), body mass index (χ2=14.224, df=3, p=0.003), history of pneumonia (χ2=6.288, df=1, p=0.012) and smoking (χ2=0.077, df=2, p=0.045) were factors that significantly influence prevalence of TB. HIV status (χ2=0.357, df=1, p=0.55) and alcohol consumption (χ2=1.664, df=1, p=0.197) were not factors that significantly influence prevalence of TB. This study concluded that 42 years of age is the median age at risk of contracting TB though all are susceptible. It also established that HIV status was not a significant factor that influences the prevalence of TB in Bumula Sub County.
Keywords: Tuberculosis; Clinical factor; Bumula; Bungoma; Kenya